2009
DOI: 10.1037/a0015812
|View full text |Cite
|
Sign up to set email alerts
|

Relations among parental acceptance and control and children’s social adjustment in Chinese American and European American families.

Abstract: Parental acceptance and control are the 2 dimensions of parenting that have been investigated most; however, little is known about their cross-cultural expressions. This longitudinal study examined acceptance, control, and R. Chao's indigenous Chinese notion of control-chiao shun (training)-in 35 immigrant Chinese American (CA) and 38 European American (EA) families. Data were collected when children were in preschool and kindergarten (T1); first and second grades (T2); and third and fourth grades (T3). Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 52 publications
2
21
0
4
Order By: Relevance
“…Although some studies support an association between parenting styles and their child's outcomes, some evidence suggests that this relation may differ across cultures (Dai, 1999;Deater-Deater-Deckard, Dodge, Bates, & Pettit, 1996;Huntsinger & Jose, 2009;Leung et al, 1998;Polaha, 1999;Steinberg et al, 1991;Stormshak et al, 2000). For instance, physical discipline has been found to be positively associated with higher externalising and aggression scores in European American children, but in African American children this correlation was negligible and non-significant (Deater-Deckard et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…Although some studies support an association between parenting styles and their child's outcomes, some evidence suggests that this relation may differ across cultures (Dai, 1999;Deater-Deater-Deckard, Dodge, Bates, & Pettit, 1996;Huntsinger & Jose, 2009;Leung et al, 1998;Polaha, 1999;Steinberg et al, 1991;Stormshak et al, 2000). For instance, physical discipline has been found to be positively associated with higher externalising and aggression scores in European American children, but in African American children this correlation was negligible and non-significant (Deater-Deckard et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, some studies have found that immigrant Chinese American parents endorse training to a greater degree than do European American parents [28,30]. However, Li et al's [3] study found no ethnic difference, but rather that mainland Chinese and European American college students perceived similar levels of training.…”
Section: Parenting Stylementioning
confidence: 85%
“…For example, regarding training's implications for academic adjustment, studies of mainland and Hong Kong Chinese college students have found positive associations of training with academic performance and efficacy [3,33]. Positive implications of training for school engagement among Chinese/Chinese American students have also emerged, including a positive link between paternal training during children's preschool years and fewer problem behaviors (including school-engagement problems) four years later for second-generation Chinese Americans [28] and indirect positive effects of both maternal and paternal guan on mainland Chinese adolescents' school engagement via the mediation of the children's xiao (filial piety) [25]. However, some studies on mainland and Hong Kong Chinese adolescents have found no association of training with their academic performance and school engagement [34,35].…”
Section: Training and Child Adjustmentmentioning
confidence: 99%
See 2 more Smart Citations